Astrocytic proteins involved in regulation of the extracellular environment are increased in the Alzheimer's disease middle temporal gyrus - Henry Liu; Adelie Y.S. Tan; Nasim F. Mehrabi; Clinton P. Turner; Maurice A. Curtis; Richard L.M. Faull; Mike Dragunow; Malvindar K. Singh-Bains; Amy M. Smith (Neurobiology of Disease)
Alzheimer's disease (AD) has complex pathophysiology involving numerous cell types and brain processes. Astrocyte involvement in AD is gaining increased attention, however a complete characterisation of astrocytic changes in the AD human brain is warranted. Astrocytes perform important homeostatic functions including regulation of the extracellular microenvironment, critical for the health of all brain cells. We have investigated changes to key astrocyte proteins involved in the regulation of CNS extracellular environment in the human AD middle temporal gyrus (MTG): aquaporin-4 (AQP-4), glutamate transporter-1 (GLT-1) and inwardly-rectifying potassium channel 4.1 (Kir4.1). We have used a high-throughput human brain tissue microarray platform with automated quantitative image analysis to measure protein changes in a large cohort of neurological control and AD cases. We found increased astrocytic glial acidic fibrillary protein (GFAP), AQP-4, GLT-1 and Kir4.1 expression that correlates with advancing Braak stage, increasing amyloid pathology and, to a greater extent, the degree of tau pathology. We confirmed that Kir4.1 immunostaining is predominantly found in astrocytes and revealed a novel redistribution of Kir4.1 protein expression into astrocytic processes in the AD MTG. Our study presents novel and potentially modifiable glial changes in the AD human brain that are critical to our understanding of disease pathogenesis.